Upgrading and regenerating method for positive electrode material on waste lithium ion battery pole piece
Through the process of cutting, baking, ultrasonic peeling, and spray drying of waste lithium battery positive slices, the problem of lithium wastewater and environmental pollution in the recycling of lithium battery orthopedic materials is solved. Essence
Patent Information
- Application Number
- CN202411943976.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
AI Technical Summary
The existing lithium battery positive electrode material recycling process has problems such as generating lithium-containing wastewater, wasting lithium resources, and using acid and alkali or organic reagents to pollute the environment.
Through the tailoring, baking and ultrasonic peeling of waste orthopedics, the hybrid system containing active materials is obtained, and particle size regulation and composition are replenished.
The composition, structure and appearance of positive pole materials are achieved, and the control of lithium wastewater is avoided, and the utilization of lithium salt is improved, and no organic solvents or acid and alkali are used to reduce environmental pollution.
Smart Images

Figure CN119381612A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials for lithium ion batteries, and in particular relates to a method for upgrading and regenerating positive electrode materials on waste lithium ion battery pole pieces. Background Art
[0002] With the rapid development of new energy vehicles, the issue of retired batteries has also attracted widespread attention. Improper handling of retired batteries can easily lead to safety and environmental problems, and is also a waste of resources such as lithium, nickel, and cobalt. It is estimated that by 2030, the annual retirement volume of ternary batteries will reach 148GWh, and the annual recycling volume of lithium, nickel, and cobalt will reach 16,000 tons of metal tons, 95,000 tons of metal tons, and 32,000 tons of metal tons, respectively. In order to achieve sustainable development of the new energy industry and promote the recycling of resources, the state has introduced various policies to encourage and promote the development of the battery recycling industry.
[0003] Lithium battery positive electrode material recycling generally adopts pyrometallurgical or wet recycling process. The traditional pyrometallurgical recycling process has a single product, high energy consumption, low recovery rate, and produces waste gas and waste residue; the traditional wet recycling process is complicated, using a large amount of acid, alkali, and organic extractants, producing waste liquid and waste residue. In order to solve the problems of long recycling process, high recycling cost, and easy environmental risks in the recycling process of existing lithium battery positive electrode material recycling process, some researchers have developed short-process positive electrode material regeneration technology. For example: Patent CN 110482617A discloses a solid phase regeneration method for waste power lithium battery ternary positive electrode material, which is obtained by collecting positive electrode materials, pre-treating materials, adding metal elements and lithium carbonate, mixing and ball milling, and finally sintering to obtain regenerated ternary positive electrode materials. Patent CN 111977704A discloses a rapid regeneration method for waste ternary lithium-ion battery positive electrode materials, which is obtained by a combined process of pre-oxidation treatment-spray drying-high temperature short-time annealing to obtain regenerated ternary positive electrode materials. Patent CN114759282A discloses a regeneration method for repairing waste lithium-ion battery positive electrode waste by simply and accurately controlling the target elements. The waste material is ultrasonically mixed with a metal salt and then calcined at high temperature to obtain a positive electrode material with an accurate element ratio and good structural stability. Patent CN 117096486A discloses a repair and regeneration method for waste lithium-ion battery positive electrode materials. The repaired and regenerated single crystal material is obtained by low-temperature melting lithium supplementation calcination and high-temperature secondary calcination. The above methods all achieve the composition control of the target product, but there are still the following disadvantages in the preparation process: the production of lithium-containing wastewater, the waste of lithium resources; the use of acid, alkali or organic reagents to pollute the environment. Summary of the invention
[0004] The present invention aims to solve the technical problems in the prior art that the lithium battery positive electrode material recovery process produces lithium-containing wastewater, wastes lithium resources, and uses acid, alkali or organic reagents to pollute the environment, and provides a method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces.
[0005] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are as follows.
[0006] The present invention provides a method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces, comprising the following steps: (1) Processing the waste positive electrode sheet to obtain a foil with active materials, peeling the active materials from the foil to obtain a mixed system containing the active materials; (2) detecting the composition of the mixed system containing the active material, and if the target ratio of the upgraded and regenerated positive electrode material is met, adjusting the particle size to obtain a processed mixed system; if the target ratio of the upgraded and regenerated positive electrode material is not met, adding a supplement to the slurry, adjusting the particle size, and obtaining a processed mixed system; (3) Drying the treated mixed system to obtain a precursor; (4) Under a protective atmosphere, the precursor is heated and calcined to obtain an upgraded and regenerated positive electrode material.
[0007] Preferably, in step (1), the processing method includes but is not limited to cutting pieces; More preferably, the waste positive electrode sheets are cut into pieces with a size no greater than 20×20 mm.
[0008] Preferably, in step (1), the treatment method includes but is not limited to roasting; More preferably, the calcination temperature is 300-550° C., the calcination time is 0.5-2 h, and the calcination atmosphere is air or oxygen.
[0009] Preferably, in step (1), the stripping process includes but is not limited to liquid phase ultrasonic stripping; More preferably, the liquid phase ultrasonic stripping time is 1-30 min, the liquid phase is deionized water, and the mass ratio of the waste positive electrode sheet to the deionized water is 1:5-20.
[0010] Preferably, in step (1), after the active material is peeled off from the foil, a separation treatment is performed to obtain a mixed system containing the active material, and the separation method includes but is not limited to screening; More preferably, the sieve for screening is a drum screen or an ultrasonic vibration screen, and the sieve has a double-layer screen, the upper layer screen is 10-100 mesh, and the lower layer screen is 200-400 mesh.
[0011] Preferably, step (1) further comprises demagnetizing the mixed system containing the active material, wherein the demagnetizing method includes but is not limited to removing iron using an electromagnetic iron remover; More preferably, the magnetic field strength of the electromagnetic iron remover is 6000-12000 Gauss.
[0012] Preferably, the method of homogenizing the mixed system containing the active material in step (1) and the method of regulating the particle size in step (2) each independently include fine grinding; More preferably, the fine grinding is performed by sand grinding with a sand grinder.
[0013] Preferably, in step (2), the particle size of the treated mixed system is less than 200 nm.
[0014] Preferably, in step (2), the supplement is one or more of a lithium source and a transition metal source; More preferably, the lithium source is one or more of lithium hydroxide monohydrate and lithium carbonate; More preferably, the transition metal element of the transition metal source is one or more of Ni, Co, and Mn; It is particularly preferred that the transition metal source is one or more of Ni hydroxide, Ni nitrate, Co hydroxide, Co nitrate, Mn hydroxide, and Mn nitrate.
[0015] Preferably, in step (2), the target ratio of the upgraded regenerated positive electrode material is: the molar ratio of lithium to transition metal is 1-1.05:1.
[0016] Preferably, in step (3), the drying treatment method includes but is not limited to spray drying; More preferably, the spray drying is carried out using a spray dryer; It is particularly preferred that the spray dryer is a two-fluid spray dryer or a centrifugal spray dryer.
[0017] Preferably, in step (3), the median particle size of the precursor is 3-15 μm.
[0018] Preferably, in step (4), the protective atmosphere is at least one of air oxygen, nitrogen, and a nitrogen-oxygen mixed gas with an oxygen content greater than 20%, the roasting temperature is 600-1000° C., and the roasting time is 5-15 h.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The method for upgrading and regenerating the positive electrode material on the pole piece of a waste lithium-ion battery of the present invention does not use organic solvents, acids or alkalis.
[0020] The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces of the present invention can realize controllable adjustment of the composition, structure and morphology of the positive electrode materials.
[0021] The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces of the present invention comprises dissolving the stripped positive electrode materials in an aqueous solution, then sand-milling and spray-drying the aqueous solution containing the positive electrode materials, evaporating the water, retaining the lithium salt and transition metal in the water, thereby improving the utilization rate of the lithium salt and avoiding the generation of lithium-containing wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The present invention is a process flow chart of the method for upgrading and regenerating the positive electrode material on the waste lithium-ion battery pole piece.
[0024] Figure 2 The electrical properties of button cells made from lithium cobalt oxide positive electrode materials regenerated from Example 4 of the present invention at different temperatures.
[0025] Figure 3 Electrochemical performance of button cells prepared from the high-nickel ternary cathode material regenerated in Example 5 of the present invention and the pristine high-nickel ternary cathode material.
[0026] Figure 4 The electrochemical performance of button cells prepared from the regenerated ternary positive electrode materials of Example 1 and Comparative Example 1 of the present invention.
[0027] Figure 5 The electrochemical performance of button cells prepared from the regenerated ternary positive electrode materials of Example 2 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0028] In order to further understand the present invention, preferred embodiments of the present invention are described below. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0029] like Figure 1 As shown, in some embodiments, the method for upgrading and regenerating the positive electrode material on the waste lithium-ion battery pole piece of the present invention comprises the following steps: (1) Cut the waste positive electrode sheet into pieces, heat and roast them, and then place them in deionized water for ultrasonic peeling. The positive electrode material (i.e., active material) is dissolved in deionized water (the water contains aluminum foil, positive electrode material, and water). After solid-liquid separation, the obtained liquid (the liquid contains positive electrode material and water) is iron-free and finely ground to homogenize the mixed system to obtain a slurry; (2) detecting the molar ratio of lithium to transition metal in the slurry, and if the molar ratio requirement of lithium to transition metal in the upgraded positive electrode material is met, continuing fine grinding to adjust the particle size to obtain a spray liquid; if the molar ratio requirement of lithium to transition metal in the upgraded positive electrode material is not met, adding one or more of a lithium source and a transition metal source to the slurry (i.e., adjusting the elemental composition) according to the molar ratio requirement of lithium to transition metal in the upgraded positive electrode material, and continuing fine grinding to adjust the particle size to obtain a spray liquid; (3) spray drying the spray liquid to obtain a precursor; (4) Under a protective atmosphere, the precursor is heated and calcined to obtain an upgraded and regenerated positive electrode material.
[0030] The principle of the above embodiment is: first, the waste positive electrode sheets are cut into pieces, roasted, etc., and then ultrasonically stripped. During the stripping process, part of the lithium will dissolve into the deionized water (conventional solid-liquid separation will cause lithium loss and lithium-containing wastewater), and then the aqueous solution containing the positive electrode material is finely ground to refine the particle size to improve the reaction capacity and achieve component homogenization. Then, the composition of the target positive electrode material is adjusted by adding lithium sources and transition metals in different molar ratios, and then the water in the aqueous solution containing the positive electrode material is evaporated by spray drying, and the positive electrode material dissolved in the water is re-dried and attached to the surface of the positive electrode sheet. The target positive electrode material size requirement is achieved by adjusting the spray drying process conditions.
[0031] In some embodiments, in step (1), the waste positive electrode sheet is preferably cut to a size of no more than 20×20 mm; the roasting temperature is 300-550°C, the roasting time is 0.5-2h, and the roasting atmosphere is air or oxygen; the ultrasonic stripping time is 1-30min, and the mass ratio of the waste positive electrode sheet to deionized water is 1:5-20; the solid-liquid separation method is sieving, the sieve is a drum sieve or an ultrasonic vibrating sieve, the sieve has a double-layer sieve, the upper sieve is 10-100 mesh, and the lower sieve is 200-400 mesh; an electromagnetic iron remover is used for iron removal, and the magnetic field strength is variable at 6000-12000 Gauss; fine grinding is performed by sand milling. A laser particle size analyzer can be used to detect the particle size distribution.
[0032] In some embodiments, in step (1), the waste positive electrode sheet is waste LiNi 0.8 Co 0.1 Mn 0.1 O2 pole piece, waste LiNi 0.4 Co 0.2 Mn0.4 One or more of, but not limited to, O2 pole pieces, waste LiCoO2 pole pieces, waste NCM622 pole pieces, waste LiMn2O4 pole pieces, waste NCM333 pole pieces, waste LiMn2O4 pole pieces, and waste lithium iron phosphate pole pieces.
[0033] In some embodiments, in step (2), the lithium source is preferably one or more of lithium hydroxide monohydrate and lithium carbonate, and the transition metal in the transition metal source is one or more of Ni, Co, and Mn. In order to avoid the influence of impurity elements, the transition metal source is preferably hydroxide, and the second choice is nitrate and other substances with volatile elements. Considering environmental protection, hydroxide is preferred, that is, the transition metal source is one or more of Ni hydroxide, Ni nitrate, Co hydroxide, Co nitrate, Mn hydroxide, and Mn nitrate. The molar ratio of lithium to transition metal in the upgraded positive electrode material is 1-1.05:1; continue to grind until the median particle size of the slurry is 100-400nm. The particle size distribution can be detected by a laser particle size analyzer, and the composition analysis can be performed by an inductively coupled plasma mass spectrometer (ICP).
[0034] In some embodiments, in step (3), spray drying is preferably performed using a spray dryer, such as a two-fluid spray dryer or a centrifugal spray dryer; and the median particle size of the precursor is 3-15 μm.
[0035] In some embodiments, in step (4), the protective atmosphere is preferably at least one of air oxygen, nitrogen, and a nitrogen-oxygen mixed gas with an oxygen content greater than 20%; the calcination temperature is 600-1000° C.; and the calcination time is 5-15 h.
[0036] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments.
[0037] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Materials, reagents, devices, instruments, equipment, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources. The slow speed in the examples is 100-300 rpm.
[0038] Example 1 The waste LiNi 0.8 Co 0.1 Mn 0.1The O2 electrode is cut into small pieces with a size not exceeding 10×10mm. The small pieces are placed in a sagger and placed in a kiln for baking at 550℃ for 2h. After cooling, they are taken out and placed in an ultrasonic cleaning machine. Deionized water is added according to the mass ratio of the electrode to deionized water of 1:10. Ultrasonication is performed for 10min. A stirring paddle is used for slow stirring during the ultrasonication process. After ultrasonication, a mixed solution 1 of aluminum foil, positive electrode material and water is obtained. The mixed solution 1 is transferred to an ultrasonic vibration screen for separation. The upper screen of the ultrasonic vibration screen is 100 mesh and the lower screen is 300 mesh. The screened material on the upper screen after sieving is a large piece of aluminum foil. The lower screen is small-sized aluminum particles, and the screened material is a mixed solution 2 of positive electrode material and water; after transferring the mixed solution 2 to a sand mill and sand grinding for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is lower than 150nm, and a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate is added according to the molar ratio of lithium to transition metal of 1.05:1, and the sand grinding is continued for 2 hours to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 750°C for 12 hours to obtain a regenerated ternary positive electrode material.
[0039] Example 2 The waste LiNi 0.4 Co 0.2 Mn 0.4 The O2 electrode is cut into small pieces with a size not exceeding 10×10mm, and the small pieces are placed in a sagger and placed in a kiln and baked at 500℃ for 2h. After cooling, the pieces are taken out and placed in an ultrasonic cleaning machine, and deionized water is added according to the mass ratio of the electrode to deionized water of 1:5. Ultrasonication is performed for 10min. A stirring paddle is used for slow stirring during the ultrasonication process. After ultrasonication, a mixed solution 1 of aluminum foil, positive electrode material and water is obtained; the mixed solution 1 is separated by a drum screen, the upper screen is 100 mesh, and the lower screen is 300 mesh. After sieving, the upper screen screen contains large pieces of aluminum foil, and the lower screen is Small-sized aluminum particles, the sieved material is a mixed solution 2 of positive electrode material and water; after transferring the mixed solution 2 to a sand mill and sand grinding for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is lower than 150nm, and a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate is added according to the molar ratio of lithium and transition metal of 1.05:1, and the sand grinding is continued for 2 hours to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 750°C for 12 hours to obtain a regenerated ternary positive electrode material.
[0040] Example 3 The waste LiCoO2 pole piece was cut into small pieces with a size not exceeding 10×10 mm, loaded into a crucible, and placed in a muffle furnace for roasting at 550°C in an atmospheric atmosphere for 2 hours. After cooling, it was taken out and placed in an ultrasonic cleaning machine, and deionized water was added according to the mass ratio of the pole piece to deionized water of 1:15. Ultrasonication was performed for 20 minutes. A stirring paddle was used for slow stirring during the ultrasonic process. After ultrasonication, a mixed solution 1 of aluminum foil, positive electrode material and water was obtained; the mixed solution 1 was transferred to an ultrasonic vibration screen for separation. The upper screen of the ultrasonic vibration screen used 50 mesh and the lower screen used 300 mesh. After sieving, the upper screen screened material was large pieces of aluminum foil, the lower screen screen was small-sized aluminum particles, and the screened material was positive electrode material and water. The mixed solution 2 is transferred to a sand mill and sand-milled for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is less than 150nm. A small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate is added according to a molar ratio of lithium to transition metal of 1.02:1, and sand-milled for 1 hour to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 800°C for 12 hours to obtain a regenerated lithium cobalt oxide positive electrode material.
[0041] Example 4 The waste LiCoO2 pole piece was cut into small pieces with a size not exceeding 10×10mm, loaded into a crucible, and placed in a muffle furnace for calcination at 450℃ in an atmospheric atmosphere for 1h. After cooling, it was taken out and placed in an ultrasonic cleaning machine, and deionized water was added according to the mass ratio of pole piece to deionized water of 1:15. Ultrasonication was performed for 30min. A stirring paddle was used for slow stirring during the ultrasonic process. After ultrasonication, a mixed solution 1 of aluminum foil, positive electrode material and water was obtained; the mixed solution 1 was transferred to an ultrasonic vibration screen for separation. The upper screen of the ultrasonic vibration screen used 50 mesh and the lower screen used 325 mesh. After sieving, the upper screen screened the large aluminum foil, the lower screen screened the small-sized aluminum particles, and the screened products were the positive electrode material and A mixed solution 2 of water; the mixed solution 2 is transferred to a sand mill and sand-milled for 4 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is less than 150nm, and a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate is added according to a molar ratio of lithium to transition metal of 1.05:1, and sand-milled for 3 hours to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 900°C for 12 hours to obtain a regenerated lithium cobalt oxide positive electrode material.
[0042] Example 5 The waste NCM622 pole pieces and the waste LiMn2O4 pole pieces were cut into small pieces with a size not exceeding 10×10 mm, and the small pieces were put into a sagger and placed in a kiln and roasted at 500°C for 2 hours. After cooling, the pieces were taken out and placed in an ultrasonic cleaning machine, and deionized water was added according to the mass ratio of the pole piece to deionized water of 1:15. Ultrasonic treatment was performed for 20 minutes. A stirring paddle was used for slow stirring during the ultrasonic process. After ultrasonic treatment, a mixed solution 1 of aluminum foil, positive electrode material and water was obtained; the mixed solution 1 was transferred to an ultrasonic vibration screen for separation. The upper screen of the ultrasonic vibration screen was 100 mesh, and the lower screen was 300 mesh. The material on the upper screen after sieving was A large piece of aluminum foil, the lower screen is small-sized aluminum particles, and the screened material is a mixed solution 2 of positive electrode material and water; after transferring the mixed solution 2 to a sand mill and sanding for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is lower than 150nm, and then a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate and nickel hydroxide are added according to the molar ratio of lithium and transition metal of 1.05:1, and the sand milling is continued for 2 hours to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 800°C for 12 hours to obtain a regenerated high-nickel ternary positive electrode material.
[0043] Example 6 The waste NCM333 pole pieces and the waste LiMn2O4 pole pieces were cut into small pieces with a size not exceeding 10×10 mm, and the small pieces were put into a sagger and placed in a kiln and roasted at 500°C for 2 hours in an atmospheric atmosphere. After cooling, the pieces were taken out and placed in an ultrasonic cleaning machine, and deionized water was added according to a mass ratio of the pole piece to deionized water of 1:8. Ultrasonic treatment was performed for 40 minutes. A stirring paddle was used for slow stirring during the ultrasonic process. After ultrasonic treatment, a mixed solution 1 of aluminum foil, positive electrode material and water was obtained. The mixed solution 1 was transferred to an ultrasonic vibration screen for separation. The upper screen of the ultrasonic vibration screen was 50 mesh, and the lower screen was 300 mesh. The sieved upper screen was the large A piece of aluminum foil, the lower screen is small-sized aluminum particles, and the screened material is a mixed solution 2 of the positive electrode material and water; the mixed solution 2 is transferred to a sand mill and sanded for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is lower than 150nm, and a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate and nickel hydroxide are added according to the molar ratio of lithium to transition metal of 1.05:1, and the sand milling is continued for 2 hours to obtain slurry 3; the slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 800°C for 12 hours to obtain a regenerated high-nickel ternary positive electrode material.
[0044] Example 7 The waste lithium iron phosphate pole pieces were cut into small pieces with a size not exceeding 10×10 mm, the small pieces were put into a sagger and placed in a kiln and roasted for 2 hours at 450°C in a protective atmosphere, and then taken out and placed in an ultrasonic cleaning machine after cooling, and deionized water was added according to a mass ratio of pole piece to deionized water of 1:15, and ultrasonic cleaning was performed for 20 minutes. A stirring paddle was used for slow stirring during the ultrasonic process, and a mixed solution 1 of aluminum foil, positive electrode material and water was obtained after ultrasonic cleaning; the mixed solution 1 was transferred to an ultrasonic vibration screen for separation, the upper screen of the ultrasonic vibration screen used a 200-mesh screen, and the lower screen used a 300-mesh screen. After screening, the upper screen screened out large pieces of aluminum foil, and the lower screen screened out The mesh is small-sized aluminum particles, and the material under the screen is a mixed solution 2 of the positive electrode material and water; after the mixed solution 2 is transferred to a sand mill and sanded for 5 hours, a small amount of the mixture is taken out and the particle size distribution is detected by a laser particle size analyzer. At this time, the particle size is lower than 150nm, and a small amount of the mixture is taken out for component analysis by ICP, and lithium hydroxide monohydrate and manganese phosphate are added according to the molar ratio of lithium to transition metal of 1.02:1, and the sand milling is continued for 2 hours to obtain slurry 3; slurry 3 is granulated by a two-fluid spray dryer to obtain a precursor; the precursor is placed in a sagger and calcined at 800°C for 12 hours to obtain a regenerated lithium manganese iron phosphate positive electrode material.
[0045] Comparative Example 1 The waste LiNi 0.8 Co 0.1 Mn 0.1 The O2 electrode is cut into small pieces with a size not exceeding 10×10 mm, the small pieces are put into a sagger and placed in a kiln and roasted at 550°C in an atmospheric atmosphere for 2 hours, taken out after cooling and placed in an ultrasonic cleaning machine, deionized water is added according to the mass ratio of the electrode to deionized water of 1:10, and ultrasonication is performed for 10 minutes. A stirring paddle is used for slow stirring during the ultrasonication process, and a mixed solution 1 of aluminum foil, positive electrode material and water is obtained after ultrasonication; the mixed solution 1 is transferred to an ultrasonic vibration screen for separation, the upper screen of the ultrasonic vibration screen adopts 100 mesh, and the lower screen adopts 300 mesh. After sieving, the upper screen screen contains large pieces of aluminum foil, the lower screen contains small-sized aluminum particles, and the screened material is a mixed solution 2 of positive electrode material and water; the mixed solution 2 is vacuum filtered, and the filter residue is placed in a vacuum oven and dried at 100°C for 12 hours to obtain a regenerated ternary positive electrode material.
[0046] Comparative Example 2 The waste LiNi 0.4 Co 0.2 Mn 0.4The O2 electrode is cut into small pieces with a size not exceeding 10×10 mm, the small pieces are put into a sagger and placed in a kiln and roasted at 550°C for 2 hours in an atmospheric atmosphere, and then taken out and placed in an ultrasonic cleaning machine after cooling, and deionized water is added according to the mass ratio of the electrode to deionized water of 1:10, and ultrasonic treatment is performed for 10 minutes. During the ultrasonic treatment, a stirring paddle is used for slow stirring, and a mixed solution 1 of aluminum foil, positive electrode material and water is obtained after ultrasonic treatment; the mixed solution 1 is transferred to an ultrasonic vibration screen for separation, the upper screen of the ultrasonic vibration screen adopts 100 mesh, and the lower screen adopts 300 mesh. After sieving, the upper screen screen contains large pieces of aluminum foil, the lower screen contains small-sized aluminum particles, and the screened material is a mixed solution 2 of positive electrode material and water; the mixed solution 2 is vacuum filtered, and the filter residue is placed in a vacuum oven and dried at 100°C for 12 hours, then taken out and placed in a sagger, and roasted at 750°C for 12 hours to obtain a regenerated ternary positive electrode material.
[0047] The regenerated positive electrode materials obtained in the above-mentioned Example 1, Example 2, Example 4, Example 5 and Comparative Example 1-2 were mixed in a mass ratio of 8:1:1 for regenerated positive electrode material: SuperP: PVDF to prepare pole pieces, metallic lithium was used as the counter electrode, 1 mol / L LiPF6 solution (EC:DEC:DMC volume ratio of 1:1:1) was used as the electrolyte, and 2032 button batteries were prepared for electrochemical performance testing, and the results are shown as follows: Figure 2-5 shown. Figure 2 The electrical properties of button cells prepared from the lithium cobalt oxide positive electrode material regenerated from Example 4 at different temperatures. Figure 3 Electrochemical performance of button cells prepared from the high-nickel ternary cathode material regenerated in Example 5 and the pristine high-nickel ternary cathode material. Figure 4 Electrochemical performance of button cells prepared from the regenerated ternary cathode materials of Example 1 and Comparative Example 1. Figure 5 The electrochemical performance of the button cells prepared from the regenerated ternary cathode materials of Example 2 and Comparative Example 2. Figure 2-5 It can be seen that through comparison, the regeneration method of the present invention can effectively improve the performance of the regenerated positive electrode material.
[0048] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces, characterized in that: The following steps are involved: (1) Processing the waste positive electrode sheet to obtain a foil with active materials, peeling the active materials from the foil to obtain a mixed system containing the active materials; (2) Detecting the composition of the mixed system containing the active material, if the target ratio of the upgraded and regenerated positive electrode material is met, adjusting the particle size to obtain a processed mixed system; If the target ratio of the upgraded and regenerated positive electrode material is not met, a supplement is added to the mixed system containing the active material to adjust the particle size and obtain a treated mixed system; (3) Drying the treated mixed system to obtain a precursor; (4) Under a protective atmosphere, the precursor is heated and calcined to obtain an upgraded and regenerated positive electrode material.
2. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (1), the processing includes cutting the waste positive electrode sheets into pieces with a size not greater than 20×20 mm.
3. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (1), the treatment includes calcination, the calcination temperature is 300-550°C, the calcination time is 0.5-2h, and the calcination atmosphere is air or oxygen.
4. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (1), the stripping method includes liquid phase ultrasonic stripping, the liquid phase ultrasonic stripping time is 1-30 minutes, the liquid phase is deionized water, and the mass ratio of the waste positive electrode sheet to the deionized water is 1:5-20.
5. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (1), after the active material is peeled off from the foil, a separation treatment is performed to obtain a mixed system containing the active material, and the separation treatment method includes screening; The sieve for screening is a drum screen or an ultrasonic vibration screen, and the sieve has a double-layer screen, the upper layer screen is 10-100 mesh, and the lower layer screen is 200-400 mesh.
6. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: Step (1) further includes demagnetizing the mixed system containing the active material, wherein the demagnetization method includes using an electromagnetic iron remover to remove iron, and the magnetic field strength of the electromagnetic iron remover for iron removal is 6000-12000 Gauss.
7. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: The method of homogenizing the mixed system containing the active material in step (1) and the method of regulating the particle size in step (2) each independently include fine grinding; The fine grinding is performed by sand grinding with a sand mill; In step (2), the particle size of the treated mixed system is less than 200 nm.
8. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (2), the supplement includes one or more of a lithium source and a transition metal source; The lithium source includes one or more of lithium hydroxide monohydrate and lithium carbonate, and the transition metal in the transition metal source includes one or more of Ni, Co, and Mn; The target ratio of the upgraded and regenerated positive electrode material is: the molar ratio of lithium to transition metal is 1-1.05:
1.
9. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (3), the drying method includes spray drying; The spray drying adopts a spray dryer, and the spray dryer is a two-fluid spray dryer or a centrifugal spray dryer. The median particle size of the precursor is 3-15 μm.
10. The method for upgrading and regenerating positive electrode materials on waste lithium-ion battery pole pieces according to claim 1, characterized in that: In step (4), the protective atmosphere during the roasting process is at least one of air, oxygen, nitrogen, and a nitrogen-oxygen mixed gas with an oxygen content of ≥20%, the roasting temperature is 600-1000° C., and the roasting time is 5-15 hours.
Citation Information
Patent Citations
Rapid regeneration method of positive electrode material of waste ternary lithium ion battery
CN111977704A
Regeneration method for repairing anode waste of waste lithium ion battery by simply and accurately regulating and controlling target element
CN114759282A
Repairing and regenerating method for positive electrode material of waste lithium ion battery
CN117096486A
Method for recycling positive material of waste lithium iron phosphate battery
CN102709620A
Method for synthesizing high-performance lithium ion battery positive electrode material by using waste lithium ion battery
CN113764762A